Comparison of the long-term clinical, metabolic, and economic outcomes of sleeve gastrectomy (SG) and roux-en-y gastric bypass (RYGB) - Bołdys-Żegocki, Hubert; Karcz, Anna; Pająk , Barbara; Wróblewska , Oliwia; Dworniczak, Małgorzata; Salash, Sofiya; Romaniuk, Aleksandra; Majewski , Jakub; Kaniecka, Maria; Koza, Artur (Quality in Sport, 2025)
Introduction: Obesity is a chronic, multifactorial disease affecting over one billion people worldwide (WHO, 2025). It increases the risk of type 2 diabetes, cardiovascular diseases and certain cancers. Because conservative treatment has limited long-term efficacy, bariatric surgery, particularly Sleeve Gastrectomy (SG) and Roux-en-Y Gastric Bypass (RYGB), has become a key therapy for morbid obesity. Aim: To compare long-term clinical, metabolic and cost-effectiveness outcomes of SG and RYGB Materials and Methods: A literature review was conducted using PubMed, PMC, Google Scholar and ResearchGate, limited to English publications. The analysis included major randomized trials and cost-effectiveness studies, as well as WHO, IFSO and national guidelines. Results: RYGB produced greater long-term weight loss, with %TWL higher by 3.6–4.9 percent, and higher diabetes remission (75 vs 61 percent at 1 year; 37 vs 27 percent at 10 years) compared with SG. It also more strongly improved insulin sensitivity and triglycerides, but carried an increased risk of nutritional deficiencies, mainly iron and vitamin B12, requiring lifelong supplementation. SG caused fewer nutritional issues but was associated with a higher incidence of GERD. Quality-of-life improvements measured by SF-36 and BAROS were similar. Cost analyses showed that RYGB, despite higher initial costs, leads to net savings within 5–10 years because of greater remission of metabolic comorbidities. Both Borisenko and Lauren confirmed its economic advantage in public health systems. Conclusions: RYGB offers superior long-term metabolic benefits and cost-effectiveness, though with higher nutritional risk. SG remains a safe and effective option, especially for patients without severe metabolic disease or GERD. The choice of procedure should be individualized, considering metabolic benefit, nutritional risk and economic factors.